Self-assessment and self-improvement as inclusive school development - Marianna Piccioli (Formare, 2022)
What are the strengths and weaknesses in the cultures, management policies and organizational practices that make an educational institution inclusive? This is the question we try to answer with this investigation, using the comparative element between the Italian and the Catalan school systems. This work is based on three theoretical frameworks: inclusive education in coherence with the Disability Studies approach; autonomy and leadership for inclusion and the self-evaluation and self-improvement processes as an inclusive school development in accordance with the perspective proposed by the Index for Inclusion. Field research reveals that the relevant legislation plays a crucial role and schools must regain a pedagogical thought in which organizational practices and management policies are based on inclusive cultural and value-based foundations.